Negative pole piece, preparation method thereof and secondary battery

By introducing inactive substances such as polymer nanofibers into the battery electrode sheet, a homogeneous negative electrode slurry is formed and a negative electrode sheet is made, the problem of degradation of the battery electrode sheet brittleness and liquid retention ability is solved, and a negative electrode sheet with high flexibility and liquid retention is achieved, which improves the battery performance and cycle life.

CN119673961APending Publication Date: 2025-03-21STATE GRID HUNAN ELECTRIC POWER COMPANY LIMITED +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411807904.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the process of improving energy density and cycle life, existing battery pole sheets have problems such as increased brittleness, difficulty in infiltration of electrolytes and decreased liquid retention capacity, resulting in reduced production yield and deterioration of battery performance.

Method used

The negative electrode sheet is composed of a current collector and a negative electrode active material layer located on at least one side of the current collector. The negative electrode active material layer contains polymer nanofibers, conductive agents and binders. Through the predispersion and secondary dispersion steps, a homogeneous negative electrode slurry is formed, and a negative electrode sheet with high flexibility and high liquid retention is prepared by coating and drying.

Benefits of technology

The flexibility and liquid retention capacity of the negative electrode sheet are achieved while improving, the saturation absorption of the electrolyte can exceed 60%, and the preparation method is simple to operate, low cost, compatible with existing battery production processes, and is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673961A_ABST
    Figure CN119673961A_ABST
Patent Text Reader

Abstract

The invention relates to a negative pole piece, a preparation method thereof and a secondary battery. The negative pole piece comprises a current collector and a negative active material layer positioned on at least one side of the current collector; the negative electrode active material layer comprises a negative electrode active material and an inactive material; wherein the inactive substance comprises a polymer nanofiber, a selectable conductive agent and a selectable binder. The preparation method of the negative pole piece comprises the following steps: dispersing polymer nanofibers into a solvent to obtain a pre-dispersion liquid; mixing the pre-dispersion liquid with a negative electrode active material, an optional conductive agent, an optional binder and a solvent, and carrying out secondary dispersion to obtain negative electrode slurry; and coating the surface of a current collector with the negative electrode slurry, and drying to obtain the negative electrode plate. The negative pole piece obtained by the negative pole piece and the preparation method disclosed by the invention has good flexibility and liquid retention property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a negative electrode plate and a preparation method thereof, and a secondary battery. Background Art

[0002] With the rapid development of electric vehicles, energy storage systems and other fields, higher and higher requirements are placed on the energy density and cycle life of batteries.

[0003] In order to meet the requirements of long battery life, the compaction density of battery materials has been continuously improved, and the thickness of pole pieces has been continuously increased; as a result, new problems have arisen: battery pole pieces are brittle, pole pieces are difficult to infiltrate with electrolyte, and the ability to retain liquid has been greatly reduced, resulting in reduced production yield and deterioration of battery performance.

[0004] Therefore, it is very important and necessary to seek a negative electrode sheet and a preparation method thereof that can simultaneously improve the flexibility and liquid retention capacity of the negative electrode sheet. Summary of the invention

[0005] In order to solve at least one of the above technical problems, the present invention provides a negative electrode plate and a preparation method thereof and a secondary battery, which can simultaneously improve the flexibility and liquid retention of the negative electrode plate of the secondary battery.

[0006] As one aspect, the present invention provides a negative electrode plate, which includes a current collector and a negative electrode active material layer located on at least one side of the current collector; the composition of the negative electrode active material layer includes negative electrode active substances and inactive substances; wherein the inactive substances include polymer nanofibers, optional conductive agents and optional binders; wherein the mass content of the negative electrode active substances in the negative electrode active material layer is 80% to 96%, for example, it can be 83%, 86%, 89%, 91%, 93%, 95, etc., and the mass content of the polymer nanofibers in the inactive substances is 10% to 100%, for example, it can be 16%, 23%, 37%, 46%, 53%, 61%, 72%, 83%, 94%, etc.

[0007] In some embodiments of the present invention, the aspect ratio of the polymer nanofiber is 50-800, for example, it can be 56, 97, 129, 168, 218, 239, 259, 286, 316, 479, 529, 668, 718, 786, etc., and the diameter is 5nm-500nm, for example, it can be 16nm, 58nm, 97nm, 136nm, 269nm, 376nm, 428nm, 489nm, etc.; and / or, the polymer nanofiber includes at least one of natural polymer nanofiber and synthetic polymer nanofiber stable in the voltage window of 1.0V-5.0V, for example, the voltage window can be 1.9V, 2.7V, 3.4V, 3.9V, 4.1V, 4.8V, etc. Among them, the synthetic polymer nanofiber has the characteristics of good electrolyte affinity and stable electrochemical window.

[0008] In some embodiments of the present invention, the natural polymer nanofibers are biomass nanofibers; preferably, the biomass nanofibers include at least one of cellulose-based nanofibers, chitin nanofibers, and silk protein nanofibers; preferably, the biomass nanofibers include at least one of unmodified biomass nanofibers and modified biomass nanofibers; preferably, the modified biomass nanofibers are obtained by subjecting unmodified biomass nanofibers to TEMPO oxidation reaction.

[0009] In some embodiments of the present invention, among the inactive substances, the mass content of biomass nanofibers is 40% to 80%, the mass content of the conductive agent is 0% to 50%, for example, it can be 5%, 11%, 18%, 26%, 39%, 43%, 49%, etc., and the mass content of the binder is 5% to 60%, for example, it can be 7%, 13%, 27%, 39%, 46%, 53%, 59%, etc.

[0010] As another aspect, the present invention provides a method for preparing the above-mentioned negative electrode sheet, which comprises the following steps: dispersing polymer nanofibers in a solvent to obtain a pre-dispersion liquid; mixing the pre-dispersion liquid with a negative electrode active material, an optional conductive agent, an optional binder and a solvent, and performing secondary dispersion to obtain a negative electrode slurry; coating the negative electrode slurry on the surface of a current collector, and drying to obtain a negative electrode sheet.

[0011] In some embodiments of the present invention, the content of polymer nanofibers in the pre-dispersion liquid is 1% to 10%, for example, it can be 3%, 6%, 7%, 8%, 9%, etc., preferably, 2% to 5%, for example, it can be 2.3%, 2.9%, 3.7%, 4.1%, 4.9%, etc.; and / or the viscosity of the pre-dispersion liquid is 500 to 5000 mPa·s, for example, it can be 594 mPa·s, 783 mPa·s, 964 mPa·s, 1289 mPa·s, 1682 mPa·s, 2596 mPa·s, 3408 mPa·s, 4129 mPa·s, 4863 mPa·s, etc.

[0012] In some embodiments of the present invention, the linear velocity of the secondary dispersion is 0.1 m / s to 15 m / s, for example, 0.3 m / s, 0.8 m / s, 1.2 m / s, 1.9 m / s, 2.3 m / s, 3.1 m / s, 4.2 m / s, 6.6 m / s, 7.1 m / s, 8.3 m / s, 9.6 m / s, 10.2 m / s, 11.6 m / s, 12.1 m / s, 13.3 m / s, 14.6 m / s, etc.; preferably, 2 m / s to 5 m / s, for example, 2.3 m / s, 2.9m / s, 3.2m / s, 3.9m / s, 4.2m / s, 4.6m / s, 4.8m / s, etc.; wherein, "linear velocity" means: for disc-type dispersion slurry, linear velocity v=nπd / 60, wherein n is the rotation speed, unit: r / min, d is the diameter of the equipment dispersion disk, unit: m; and / or, the time for secondary dispersion is 30min to 300min, for example, 32min, 97min, 136min, 196min, 216min, 268min, 295min, etc.

[0013] In some embodiments of the present invention, the solid content of the negative electrode slurry is 30% to 76%, for example, 32%, 46%, 51%, 58%, 69%, 74%, etc.; and / or the drying temperature is 30°C to 100°C, for example, 36°C, 48°C, 56°C, 63°C, 72°C, 87°C, 91°C, 98°C, etc., preferably, 40°C to 90°C, for example, 42°C, 48°C, 51°C, 59°C, 63°C, 69°C, 73°C, 79°C, 83°C, 89°C, etc.

[0014] In some embodiments of the present invention, the current collector includes any one of copper foil, carbon-coated copper foil, aluminum foil, carbon-coated aluminum foil, composite copper foil, and composite aluminum foil; and / or the solvent is water.

[0015] As another aspect, the present invention provides a secondary battery, which comprises the negative electrode sheet mentioned above or the negative electrode sheet obtained by the above preparation method.

[0016] The technical solution provided by the embodiment of the present invention has the following advantages:

[0017] The negative electrode plate of the present invention has excellent flexibility and liquid retention capacity, and has improved flexibility compared to the plate prepared by the traditional method. The electrolyte saturation absorption capacity of the negative electrode plate of the present invention can exceed 60%.

[0018] In the preparation method of the negative electrode plate of the present invention, the step of selecting biomass nanofibers with a high aspect ratio and pre-dispersing them can effectively improve the dispersion degree of biomass nanofibers in the subsequent negative electrode slurry. The biomass nanofiber pre-dispersion liquid is added to the negative electrode slurry, the inactive substances are partially / completely replaced, and the biomass nanofibers are dispersed at a low speed to form a homogeneous negative electrode slurry; wherein, by accurately controlling the line speed and time, it is ensured that the biomass nanofibers do not break, and the flexibility in the later stage is guaranteed. After coating and drying, a highly flexible and liquid-retaining negative electrode plate is made; wherein, the flexibility comes from the nanonetwork formed by one-dimensional nanofibers, the high specific surface area of ​​the nanofibers themselves has good adsorption, and the polar groups have good affinity for the electrolyte molecules, so the electrolyte can be stably locked. In addition, the preparation method of the present invention also has the advantages of high preparation efficiency, low cost, and simple operation, which is compatible with the existing battery production process and can meet large-scale applications.

[0019] When the negative electrode sheet of the present invention and the negative electrode sheet obtained by the preparation method of the present invention are used to prepare a secondary battery, the metal precipitation of the secondary battery is small and the cycle stability is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0022] Figure 1 Schematic diagram of the preparation principle of the negative electrode sheet according to an embodiment of the present invention;

[0023] Figure 2 is a scanning electron microscope image of the cellulose nanofibers used in Examples 1 to 3 of the present invention;

[0024] Figure 3 This is a test diagram of the electrolyte contact angle of the negative electrode sheet prepared in Example 9 of the present invention;

[0025] Figure 4 This is a test diagram of the electrolyte contact angle of the negative electrode sheet prepared in Comparative Example 1 of the present invention;

[0026] Figure 5 This is a macroscopic state diagram of a fully charged and disassembled negative electrode sheet of a secondary battery prepared by the negative electrode sheet of Example 9 of the present invention after cycling;

[0027] Figure 6 This is a macroscopic state diagram of the negative electrode sheet of the secondary battery prepared by the negative electrode sheet of Comparative Example 1 of the present invention after cycling, with the negative electrode sheet fully disassembled. DETAILED DESCRIPTION

[0028] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0029] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0030] According to an embodiment of the present invention, a negative electrode plate is provided, which includes a current collector and a negative electrode active material layer located on at least one side of the current collector; the composition of the negative electrode active material layer includes negative electrode active substances and inactive substances; wherein the inactive substances include polymer nanofibers, optional conductive agents and optional binders; wherein the mass content of the negative electrode active substances in the negative electrode active material layer is 80% to 96%, and the mass content of the polymer nanofibers in the inactive substances is 10% to 100%.

[0031] According to an embodiment of the present invention, a method for preparing the above-mentioned negative electrode sheet is provided, and the preparation method comprises the following steps: dispersing polymer nanofibers in a solvent to obtain a pre-dispersion liquid; mixing the pre-dispersion liquid with a negative electrode active material, an optional conductive agent, an optional binder and a solvent, and performing secondary dispersion to obtain a negative electrode slurry; coating the negative electrode slurry on the surface of a current collector, and drying to obtain a negative electrode sheet.

[0032] The negative electrode sheet obtained by the preparation method of the embodiment of the present invention has good flexibility and liquid retention ability.

[0033] In some embodiments of the present invention, the negative electrode sheet has good flexibility and liquid retention ability. Figure 1 shown. Figure 1 Schematic diagram of the preparation principle of the negative electrode sheet of the embodiment of the present invention. Figure 1In the paper, natural polymer nanofibers are used as an example to explain as follows: one-dimensional natural polymer nanofibers have high mechanical strength, good flexibility, high specific surface area and rich polar functional groups. The benefits of introducing natural polymer nanofibers into the negative electrode slurry are: physical interweaving and hydrogen bonding are used to form a continuous network to improve the flexibility of the electrode. In addition, the interaction of functional groups and the unique adsorption of nanomaterials lock the electrolyte molecules (among which, Figure 1 The electrolyte molecules in the battery are ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC), thereby achieving simultaneous improvement in flexibility and liquid retention capacity.

[0034] In some embodiments of the present invention, a method for preparing a negative electrode sheet comprises the following steps:

[0035] (1) Pre-dispersing biomass nanofibers to obtain a pre-dispersion liquid; the solid content of the pre-dispersion liquid is 1% to 10%, for example, it can be 1.9%, 3.6%, 5.2%, 7.3%, 9.8%, etc.; the viscosity is 500 to 5000 mPa·s, for example, it can be 568 mPa·s, 1239 mPa·s, 1986 mPa·s, 2896 mPa·s, 3268 mPa·s, 3908 mPa·s, 4639 mPa·s, etc.

[0036] (2) The pre-dispersion liquid obtained in step (1) is mixed with a negative electrode active material, an optional conductive agent, an optional binder and a solvent, and a secondary dispersion is performed to obtain a negative electrode slurry; wherein the mass content ratio of the biomass nanofibers in the inactive material is 1% to 100%, for example, it can be 13%, 28%, 43%, 62%, 78%, 82%, 97%, etc.; then, the secondary dispersion is performed at a linear speed of 0.1m / s to 15m / s, for example, the linear speed can be 1.8m / s, 3.1m / s, 4.2m / s, 5.9m / s, 6.7m / s, 8.6m / s, 9.8m / s, 11.9m / s, 12.7m / s, 13.6m / s, 14.8m / s, etc., to obtain a homogeneous negative electrode slurry.

[0037] (3) The homogeneous negative electrode slurry obtained in step (2) is coated on the surface of the current collector and dried at 30°C to 100°C, for example, 36°C, 52°C, 72°C, 81°C, 89°C, 93°C, 97°C, etc., to obtain a negative electrode sheet with high flexibility and high liquid retention capacity.

[0038] In some embodiments of the present invention, in step (1), the biomass nanofibers include at least one of modified or unmodified cellulose-based nanofibers, modified or unmodified chitin nanofibers, modified or unmodified silk protein nanofibers, modified or unmodified cellulose-based electrospun nanofibers, modified or unmodified chitin electrospun nanofibers, and modified or unmodified silk protein electrospun nanofibers.

[0039] In some embodiments of the present invention, in step (1), preferably, the solid content of the pre-dispersion liquid is 2% to 5%, for example, it can be 2.6%, 3.1%, 3.6%, 3.9%, 4.6%, etc. When the solid content of the pre-dispersion liquid is 2% to 5%, the homogeneous negative electrode slurry obtained in step (2) has better dispersion stability.

[0040] In some embodiments of the present invention, in step (2), preferably, the mass content ratio of biomass nanofibers in the inactive substance is 40% to 80%, for example, it can be 43%, 51%, 59%, 64%, 71%, 89%, etc.

[0041] In some embodiments of the present invention, in step (2), preferably, the linear velocity of the secondary dispersion is 2 to 5 m / s, for example, 2.9 m / s, 3.4 m / s, 3.9 m / s, 4.3 m / s, 4.9 m / s, etc.

[0042] In some embodiments of the present invention, in step (2), the composition of the homogenized negative electrode slurry includes a negative electrode active material, a conductive agent, a binder, water and biomass nanofibers.

[0043] In some embodiments of the present invention, in step (3), preferably, the drying temperature is 40°C to 90°C, for example, it can be 41°C, 49°C, 56°C, 63°C, 72°C, 79°C, 86°C, etc.

[0044] According to an embodiment of the present invention, a secondary battery is provided, and the secondary battery comprises the above-mentioned negative electrode plate or the negative electrode plate obtained by the above-mentioned preparation method.

[0045] In order to further illustrate the effect of the present invention, specific embodiments are used for description below.

[0046] The following examples and comparative examples are all lithium iron phosphate-graphite battery systems.

[0047] Example 1

[0048] A method for preparing a negative electrode sheet:

[0049] (1) pre-dispersing cellulose nanofibers with an aspect ratio of 100 in water to obtain a pre-dispersion liquid with a solid content of 2% and a viscosity of 2500 mPa·s;

[0050] (2) 1880 g of graphite, a negative electrode active material, 3000 g of the pre-dispersion liquid obtained in step (1), 30 g of conductive agent SP (Super Li), 30 g of binder CMC, and 60 g of solvent water were mixed, and then secondary dispersion was performed at a linear speed of 5 m / s for 0.5 h to obtain a homogeneous negative electrode slurry;

[0051] (3) According to the established process, the homogeneous negative electrode slurry obtained in step (2) is coated on the surface of the copper foil current collector, and dried at a temperature of 55° C. to obtain a negative electrode sheet.

[0052] Example 2

[0053] Except for step (1) "the viscosity is 2455 mPa·s" and step (2) "1880 g of negative electrode active material graphite, 2400 g of the pre-dispersion liquid obtained in step (1), 30 g of conductive agent SP (Super Li), 42 g of binder CMC, and 648 g of solvent water are mixed, and then the negative electrode slurry is secondary dispersed at a linear speed of 2 m / s", the remaining steps are the same as in Example 1, as shown in Table 1.

[0054] Example 3

[0055] Except for step (2) "mixing 1880 g of negative electrode active material graphite, 2700 g of the pre-dispersion obtained in step (1), 30 g of conductive agent SP (Super Li), 36 g of binder CMC, and 354 g of solvent water, and then secondary dispersing the negative electrode slurry at a linear speed of 3 m / s", the remaining steps are the same as in Example 1, as shown in Table 1.

[0056] Example 4

[0057] Except for step (1) "viscosity is 2300mPa·s", step (2) "mixing 1880g of negative electrode active material graphite, 2400g of pre-dispersed liquid obtained in step (1), 30g of conductive agent SP (Super Li), 42g of binder CMC, and 648g of solvent water, and then dispersing the negative electrode slurry at a linear speed of 2m / s", the remaining steps are the same as in Example 1, as shown in Table 1.

[0058] Example 5

[0059] Except for step (1) "viscosity is 2300 mPa·s"; step (2) "mixing 1880 g of negative electrode active material graphite, 2700 g of the pre-dispersion obtained in step (1), 30 g of conductive agent SP (Super Li), 36 g of binder CMC, and 354 g of solvent water, and then secondary dispersing the negative electrode slurry at a linear speed of 3 m / s", the remaining steps are the same as in Example 1, as shown in Table 1.

[0060] Example 6

[0061] Except for step (1) "viscosity is 2300 mPa·s", the remaining steps are the same as those in Example 1, as shown in Table 1.

[0062] Example 7

[0063] Except for step (1) "using TEMPO oxidized cellulose nanofibers" and "viscosity of 3000 mPa·s"; step (2) "mixing 1880 g of negative electrode active material graphite, 2400 g of the pre-dispersion liquid obtained in step (1), 30 g of conductive agent SP (Super Li), 42 g of binder CMC, and 648 g of solvent water, and then performing secondary dispersion of the negative electrode slurry at a linear speed of 2 m / s", the remaining steps are the same as those in Example 1, as shown in Table 1.

[0064] Among them, the preparation method of TEMPO oxidized cellulose nanofibers is: dissolve 1.0g TEMPO reagent and 10g NaBr in 5000mL deionized water; then disperse 50g of formic acid treated bamboo pulp in the above solution, slowly add NaClO solution under stirring, and then drip dilute hydrochloric acid therein to control the pH at about 10.2. As the reaction proceeds, continuously drip dilute NaOH solution to adjust the pH of the reaction system. After 2h, add 50mL ethanol to terminate the reaction, and finally filter and wash the product with deionized water to neutrality to obtain TEMPO oxidized nanocellulose.

[0065] Example 8

[0066] Except for step (1) "using TEMPO oxidized cellulose nanofibers" and "viscosity of 3000 mPa·s"; step (2) "mixing 1880 g of negative electrode active material graphite, 2700 g of the pre-dispersion liquid obtained in step (1), 30 g of conductive agent SP (Super Li), 36 g of binder CMC, and 354 g of solvent water, and then performing secondary dispersion of the negative electrode slurry at a linear speed of 3 m / s", the remaining steps are the same as those in Example 1, as shown in Table 1.

[0067] Among them, the preparation method of TEMPO oxidized cellulose nanofibers is: dissolve 1.0g TEMPO reagent and 10g NaBr in 5000mL deionized water; then disperse 50g of formic acid treated bamboo pulp in the above solution, slowly add NaClO solution under stirring, and then drip dilute hydrochloric acid therein to control the pH at about 10.2. As the reaction proceeds, continuously drip dilute NaOH solution to adjust the pH of the reaction system. After 2h, add 50mL ethanol to terminate the reaction, and finally filter and wash the product with deionized water to neutrality to obtain TEMPO oxidized nanocellulose.

[0068] Example 9

[0069] Except for step (1) "using TEMPO oxidized cellulose nanofibers" and "viscosity of 3000 mPa·s", the remaining steps are the same as those in Example 1, as shown in Table 1.

[0070] Among them, the preparation method of TEMPO oxidized cellulose nanofibers is: dissolve 1.0g TEMPO reagent and 10g NaBr in 5000mL deionized water; then disperse 50g of formic acid treated bamboo pulp in the above solution, slowly add NaClO solution under stirring, and then drip dilute hydrochloric acid therein to control the pH at about 10.2. As the reaction proceeds, continuously drip dilute NaOH solution to adjust the pH of the reaction system. After 2h, add 50mL ethanol to terminate the reaction, and finally filter and wash the product with deionized water to neutrality to obtain TEMPO oxidized nanocellulose.

[0071] The contact angle test results of the prepared negative electrode sheet on the electrolyte after rolling are as follows: Figure 3 shown.

[0072] Comparative Example 1

[0073] (1) 1880 g of negative electrode active material graphite, 60 g of conductive agent SP (Super Li), 60 g of binder CMC, and 3000 g of solvent water were mixed, and then secondary dispersion was performed at a linear speed of 5 m / s for 0.5 h to obtain a homogeneous negative electrode slurry;

[0074] (2) According to the established process, the homogeneous negative electrode slurry obtained in step (2) is coated on the surface of the copper foil current collector, and dried at a temperature of 55° C. to obtain a negative electrode sheet, as shown in Table 1.

[0075] The contact angle test results of the prepared negative electrode sheet on the electrolyte after rolling Figure 4 shown.

[0076] Comparative Example 2

[0077] Except for step (1) "pre-dispersing cellulose nanofibers with an aspect ratio of 10 in water", the remaining steps are the same as those in Example 1, as shown in Table 1.

[0078] Comparative Example 3

[0079] Except for step (2) "secondary dispersion of the negative electrode slurry at a linear velocity of 20 m / s", the remaining steps are the same as those in Example 1, as shown in Table 1.

[0080] Comparative Example 4

[0081] Except for step (1) "pre-dispersing cellulose nanofibers with an aspect ratio of 500 in water", the remaining steps are the same as those in Example 1, as shown in Table 1.

[0082] Performance Testing

[0083] (1) The positive electrode sheets are respectively matched with the negative electrode sheets obtained in Examples 1 to 9 and Comparative Examples 1 to 4 to prepare battery cells, and the battery cells are placed in shells and injected with liquid according to normal battery production processes to prepare batteries. The positive electrode sheets are lithium iron phosphate sheets, which contain lithium iron phosphate, carbon black, and PVDF in a mass ratio of 95:2.5:2.5. The electrolyte composition is: the solvent is ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC); the solute is lithium hexafluorophosphate LiPF 6 , the volume ratio of various substances in the solvent: EC:DMC:EMC=1:1:1, and the concentration of lithium hexafluorophosphate in the solvent is 1 mol / L.

[0084] (2) The different batteries obtained in step (1) were subjected to a 0.5C charge-discharge cycle in the voltage range of 2.0 to 3.6 V. After 200 cycles, the batteries were fully charged and disassembled to observe the lithium deposition state of the negative graphite electrode. The test results are shown in Table 2.

[0085] Among them, the calculation formula for the saturated liquid absorption of the electrode electrolyte is:

[0086] Electrode saturated electrolyte absorption η (%) = (electrolyte absorption saturation after the electrode mass m 1 - Foil mass m 2 ) / (mass of unabsorbed electrolyte electrode m 3 - Foil mass m 2 )×100%.

[0087] The macroscopic picture of the negative electrode sheet of the battery prepared by using the negative electrode sheet of Example 9 after full charge disassembly after cycling is as follows: Figure 5 The macroscopic picture of the negative electrode sheet of the battery prepared by using the negative electrode sheet of Comparative Example 1 after full charge disassembly after cycling is as shown in Figure 6 shown.

[0088] Table 1 Preparation conditions of negative electrode sheets of Examples 1 to 9 and Comparative Examples 1 to 4

[0089]

[0090]

[0091] Table 2 Performance test results of negative electrode sheets of Examples 1 to 9 and Comparative Examples 1 to 4

[0092]

[0093] Performance test results analysis:

[0094] (1) Figure 2 The scanning electron microscope (SEM) images of the cellulose nanofibers used in Examples 1 to 3 of the present invention are shown.

[0095] (2) Figure 3 This is a graph showing the contact angle test results of the negative electrode sheet prepared in Example 9 of the present invention on the electrolyte after rolling. Figure 4 This is a test result of the contact angle of the negative electrode sheet prepared in Comparative Example 1 of the present invention to the electrolyte after rolling. Figure 3 and Figure 4 From the comparison results, it can be seen that the introduction of biomass nanofibers can significantly improve the affinity of the negative electrode sheet to the electrolyte.

[0096] (2) According to the data comparison results in Table 2, it can be seen that:

[0097] ① Adding any suitable nanofiber polymer will enhance the bending resistance of the electrode.

[0098] ② From the comparison results of Example 1 and Comparative Example 2, it can be seen that when the aspect ratio of the biomass nanofibers is too small, a continuous network cannot be constructed, thereby failing to improve the flexibility of the negative electrode sheet.

[0099] ③The introduction of biomass nanofibers can increase the saturated liquid absorption of the negative electrode electrolyte, and the saturated liquid absorption of the electrolyte increases with the increase in the amount of biomass nanofibers added.

[0100] (3) Figure 5 This is a macroscopic state diagram of a battery prepared with the negative electrode sheet of Example 9 of the present invention after full charge and disassembly of the negative electrode sheet; Figure 6 This is a macroscopic state diagram of the negative electrode sheet of the comparative example 1 of the present invention after the battery is fully charged and disassembled after cycling.

[0101] from Figure 5 It can be seen from the figure that thanks to the introduction of nanocellulose, after the battery has been cycled the same number of times, the surface of the electrode is golden and no obvious lithium deposition occurs.

[0102] from Figure 6 It can be seen from the figure that the negative electrode prepared by the conventional method shows obvious lithium deposition after cycling.

[0103] According to the above data analysis, it can be concluded that the preparation method of the embodiment of the present invention can simultaneously improve the flexibility of the negative electrode sheet and the electrolyte retention.

[0104] In summary, the method for preparing the negative electrode sheet of the embodiment of the present invention is simple to operate, and can simultaneously improve the flexibility and liquid retention capacity of the negative electrode sheet battery, thereby further helping to improve the battery cycle life. In addition, the method for preparing the negative electrode sheet of the embodiment of the present invention also has a good commercial application prospect.

[0105] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0106] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A negative electrode plate, characterized in that: The negative electrode plate comprises a current collector and a negative electrode active material layer located on at least one side of the current collector; The negative electrode active material layer comprises a negative electrode active material and an inactive material; Wherein, the inactive material comprises polymer nanofibers, an optional conductive agent and an optional binder; The mass content of the negative electrode active material in the negative electrode active material layer is 80% to 96%, and the mass content of the polymer nanofiber in the inactive material is 10% to 100%.

2. The negative electrode sheet according to claim 1, characterized in that: The polymer nanofiber has an aspect ratio of 50 to 800 and a diameter of 5 nm to 500 nm; And / or, the polymer nanofibers include at least one of natural polymer nanofibers and synthetic polymer nanofibers that are stable within a voltage window of 1.0V to 5.0V.

3. The negative electrode sheet according to claim 2, characterized in that: The natural polymer nanofibers are biomass nanofibers; Preferably, the biomass nanofibers include at least one of cellulose-based nanofibers, chitin nanofibers, and silk protein nanofibers; Preferably, the biomass nanofibers include at least one of unmodified biomass nanofibers and modified biomass nanofibers; Preferably, the modified biomass nanofibers are obtained by subjecting unmodified biomass nanofibers to TEMPO oxidation reaction.

4. The negative electrode sheet according to claim 3, characterized in that: In the inactive material, the mass content of the biomass nanofiber is 40% to 80%, the mass content of the conductive agent is 0% to 50%, and the mass content of the binder is 5% to 60%.

5. A method for preparing a negative electrode sheet according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: dispersing the polymer nanofibers in a solvent to obtain a pre-dispersion liquid; The pre-dispersed liquid is mixed with a negative electrode active material, an optional conductive agent, an optional binder and a solvent, and a secondary dispersion is performed to obtain a negative electrode slurry; The negative electrode slurry is coated on the surface of the current collector and dried to obtain a negative electrode sheet.

6. The preparation method according to claim 5, characterized in that: In the pre-dispersion liquid, the content of polymer nanofibers is 1% to 10%, preferably 2% to 5%; And / or, the viscosity of the pre-dispersion liquid is 500 to 5000 mPa·s.

7. The preparation method according to claim 5 or 6, characterized in that: The linear velocity of the secondary dispersion is 0.1m / s to 15m / s, preferably 2m / s to 5m / s; And / or, the secondary dispersion time is 30 min to 300 min.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The solid content of the negative electrode slurry is 30% to 76%; And / or, the drying temperature is 30°C to 100°C, preferably, 40°C to 90°C.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The current collector comprises any one of copper foil, carbon-coated copper foil, aluminum foil, carbon-coated aluminum foil, composite copper foil, and composite aluminum foil; And / or, the solvent is water.

10. A secondary battery, characterized in that: The secondary battery comprises the negative electrode sheet according to any one of claims 1 to 4 or the negative electrode sheet obtained by the preparation method according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Flexible lithium ion battery electrode plate with self supporting capability and preparation method thereof

    CN105633343A

  • Preparation method of flexible pole piece

    CN107369811A

  • Electrode, secondary battery, battery pack, and vehicle

    CN109819684A

  • Negative electrode binder, negative electrode plate and lithium ion battery

    CN118406455A

  • Composition for nonaqueous electrolyte battery electrodes and additive for nonaqueous electrolyte battery electrodes

    WO2024143508A1